2007
DOI: 10.1071/ea06064
|View full text |Cite
|
Sign up to set email alerts
|

FutureDairy: a national, multidisciplinary project to assist dairy farmers to manage future challenges - methods and early findings

Abstract: FutureDairy is a national, multidisciplinary project designed to assist Australian dairy farmers to manage future challenges. FutureDairy is exploring technical, economic and social aspects of technology adoption through an innovative approach that combines methodologies of social research (‘People’), extension (‘System’) and technical research (‘Science’). The technologies being investigated revolve around increasing forage production per unit of land through a complementary forage rotation; evaluating the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Incorporation of principles of a complementary forage system ( Farina et al, 2011 ) and high yielding forages may provide an opportunity to grow more feed in a small area compared to traditional pastures (e.g. 17 t dry matter [DM]/ha) ( Garcia et al, 2007a ) thereby reducing average walking distances. Analysis of two years of historical data from a pasture-based AMS research herd has indicated the number of extended milking intervals (>16 h intervals between consecutive milkings) was increased when cows were grazing paddocks in excess of 800 m from the dairy.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of principles of a complementary forage system ( Farina et al, 2011 ) and high yielding forages may provide an opportunity to grow more feed in a small area compared to traditional pastures (e.g. 17 t dry matter [DM]/ha) ( Garcia et al, 2007a ) thereby reducing average walking distances. Analysis of two years of historical data from a pasture-based AMS research herd has indicated the number of extended milking intervals (>16 h intervals between consecutive milkings) was increased when cows were grazing paddocks in excess of 800 m from the dairy.…”
Section: Introductionmentioning
confidence: 99%
“…Pasture systems are limited in terms of their ability to supply high amounts of quality forages to support the requirements of dairy cows throughout the year. Therefore, there is a need to consider alternative forage production systems such as complementary forage rotation (CFR) systems (Garcia and Fulkerson, 2005, Garcia et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This particularly relates to the use of inorganic fertilizers and the risks of contaminating underground water courses by leaching of nutrients. Consequently, there is a need to investigate new production systems that can accommodate substantial gains in the productivity of dairy cows to take advantage of current upward trends in dairy commodity prices with minimum or no adverse effects on the environment (Garcia et al. , 2007a,b).…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, an experiment was conducted in Australia for three consecutive years to compare DM production, nutritive value of DM produced and nutrient‐ and water‐use efficiency of a CFR system with a grass pasture system. This experiment is part of a major research programme, FutureDairy, which includes extension, development and social research (Garcia et al. , 2007a).…”
Section: Introductionmentioning
confidence: 99%